2015
DOI: 10.1007/s12197-015-9328-4
|View full text |Cite
|
Sign up to set email alerts
|

Financial competence, overconfidence, and trusting investments: Results from an experiment

Abstract: Financial transactions sometimes occur in an environment where third-party enforcement is lacking. Behavioral explanations typically allude to the social preferences, where an individual's utility is directly affected by another's outcome, as the driver of the trusting investments and reciprocal returns. We hypothesize that, in part, these decisions are determined by an individual's financial literacy and overconfidence in one's knowledge. Experimental evidence is coupled with an innovative financial literacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…In an important study of stock trading behavior, researchers found that over-confidence was associated with higher levels of trading and lower portfolio returns for online traders (Barber and Odean 2001). Other researchers also found that over-confidence was a significant determinant of risky financial behavior: over-confident individuals made larger contributions in an investment game and were willing to take greater investment risk (McCannon et al 2015).…”
Section: Other Demographic and Psychographic Variablesmentioning
confidence: 99%
“…In an important study of stock trading behavior, researchers found that over-confidence was associated with higher levels of trading and lower portfolio returns for online traders (Barber and Odean 2001). Other researchers also found that over-confidence was a significant determinant of risky financial behavior: over-confident individuals made larger contributions in an investment game and were willing to take greater investment risk (McCannon et al 2015).…”
Section: Other Demographic and Psychographic Variablesmentioning
confidence: 99%
“…In terms of investing behavior, overconfidence leads to excessive trading and under‐diversification. In experimental markets, overconfident individuals trade more (Deaves, Lüders, and Luo, 2009) and make larger contributions in an investment game (McCannon, Asaad, & Wilson, 2016). Barber and Odean (2000) find that overconfidence and excessive trading lead to trading costs and poor performance.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…This is in line with recent research by Von Gaudecker (2015), who finds that most losses from lacking diversification are incurred by overconfident investors. McCannon et al (2016) show that overconfident clients, who believe they possess more knowledge and understanding than they actually do, lead investors to underestimate risks and shortcomings of certain investment options, although results by Hackethal et al (2012) suggest that such biased behavior seems to diminish with experience.…”
Section: Neglected Factors In the Analysis Of Financial Behaviormentioning
confidence: 99%